Pengembangan Sistem Informasi Akademik Surat Masuk dan Surat Keluar di Rumpun Matematika FMIPA UNJ Berbasis Website - Dwi Solihatun (Universitas Negeri Jakarta, 2022)
Letter is a written communication media made by one party and addressed to another party. The existence of letters cannot be replaced by technology that is currently developing, because letters are considered as authentic evidence in black over white. Communication in the form of correspondence will never be abandoned, either personally or by government agencies/organizations. One of the agencies that use correspondence as a means of communication is the Mathematics Clump of the Faculty of Mathematics and Natural Sciences (FMIPA) UNJ which consists of four Study Programs. This thesis aims to develop an Academic Information System for Incoming and Outgoing Letters in the Mathematics Clump of FMIPA UNJ which can help process correspondence in the Mathematics Clump of FMIPA UNJ online. Software development method (Software Development Life Cycle) with the Spiral model. The implementation stage of this system uses the MVC (Model View Controller) concept with the help of framework. At the end of the development, the system is tested using the Black Box which consists of functional tests and non-functional tests or usability tests. The test was carried out using a User Acceptance Test (UAT) questionnaire. The results of the functional test of 91.2% are obtained, it can be said that functionally the whole system is running well and as needed. And the non-functional test results are worth 93.2%, it can be said that the usability value of the whole system gets a very decent predicate.